Speed Control of Induction Motor using Digital Signal Processor TMS320F28027F - Awaar Vinay Kumar; M.N Sandhya Rani; Naragani Pravardh; Talluri Sasidhar; Polisetty Samanvita; Vakkalanka Satya Sreyas; Al-Jawahry Hassan Mohmmed (E3S Web of Conferences, 2023)
Single-phase induction motors are widely used today. A single-phase induction motor is operated using a single-phase inverter. The Single-phase inverter consists of four MOSFETs, two for the high side and two for the low side. The Single-phase induction motors are a constant speed motor. As a corollary, the speed control of the Single-Phase Induction motor becomes a very important necessity. Speed control of the Single-Phase Induction motor can be done in many ways. The method followed in this paper is voltage control/ (V/F Control). By controlling the duty cycle of the MOSFETs, we can control the output of the inverter and there by control the speed of the Single-Phase Induction motor. The inverter has been interfaced with MATLAB, which generates pulses and sends them to the Digital Signal processor. Texas Instrument’s low-cost Piccolo F2802x MCUs are ideal for a variety of applications, such as washing machines, compressors, pumps, fans, electric bicycles, tools, treadmills, compact drives, sewing and textile machines, lifts and hobby motors. This paper focuses on closed loop control of single-phase induction motor using this Micro Controller, F2802x Digital Signal Processor using feedback obtained through a Hall Sensor.